Pemberdayaan Pekerja UMKM untuk Mengenal dan Sadar akan Pentingnya Hygiene Sanitasi pada UMKM - Jordan Syah Gustav; Sumardiyono Sumardiyono; Warda Yussy Rha; Farhana Syahrotun Nisa S; Maria Paskanita Widjanarti; Seviana Rinawati; Lusi Ismayenti; Tutug Bolet Atmojo; Bekti Utomo; Miftachurrohman Miftachurrohman; Nirwana Putri Azzahra; Ajay Abdiel Ferrall; Ica Yuniar (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service activity aimed to increase the knowledge and awareness of Micro, Small, and Medium Enterprises (MSME) workers regarding the importance of hygiene and sanitation in food production processes. The program was carried out at Kripik Tempe “Tri Manunggal” in Karangsari Village, Jatiyoso Subdistrict, Karanganyar Regency, using a participatory and educational approach. Participants received training that included material presentation, handwashing simulation, and the use of personal protective equipment (PPE). Evaluation was conducted through pre-tests and post-tests to measure knowledge improvement. Descriptive analysis showed a significant increase in the average score from 20% (pre-test) to 90% (post-test). In addition to cognitive gains, participants also showed behavioral changes and a willingness to apply and promote hygiene practices within their communities. The program was supported by providing sanitation facilities such as handwashing stations and PPE kits. In conclusion, hygiene and sanitation education is highly effective in fostering clean working behavior among food-sector MSME and is suitable for replication in similar community.